Transparent electroconductive film

The transparent conductive film, featuring a polymer matrix and metal fibers with a surface roughness of 1.5 nm or more, addresses the flexibility and conductivity issues of conventional films, providing a defect-free and reliable conductive layer.

JP2025061587AInactive Publication Date: 2025-04-10NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025009042
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional transparent conductive films with metal oxide layers are inflexible and prone to cracking under physical stress, while films with metal fiber conductive layers suffer from conductivity defects due to contact and friction.

Method used

A transparent conductive film comprising a substrate with a transparent conductive layer made of a polymer matrix and metal fibers, where the arithmetic average surface roughness (Ra) of the conductive layer is 1.5 nm or more, preventing conductivity defects even under contact and friction.

Benefits of technology

The film maintains excellent conductivity without defects, even when rolled or laminated, due to the enhanced bonding between metal fibers and the polymer matrix, ensuring reliable performance across various applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061587000001_ABST
    Figure 2025061587000001_ABST
Patent Text Reader

Abstract

To provide a transparent electroconductive film that comprises an electroconductive layer containing metal fibers but is unsusceptible to poor electroconductivity due to contact.SOLUTION: This transparent electroconductive film comprises a base material and a transparent electroconductive layer disposed on at least either side of the base material. The transparent electroconductive layer includes a polymer matrix and metal fibers present in the polymer matrix. The arithmetic average surface roughness Ra of the transparent electroconductive layer is 1.5 μm or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film. [Background technology]

[0002] Conventionally, transparent conductive films that have a metal oxide layer such as an indium tin oxide layer (ITO layer) formed on a resin film have been widely used as transparent conductive films for use in electrodes of touch sensors, etc. However, transparent conductive films with a metal oxide layer formed on them have the problem that they are insufficient in bendability and are prone to cracking due to physical stress such as bending.

[0003] Also, a transparent conductive film having a conductive layer containing metal fibers made of silver, copper, etc. has been proposed as a transparent conductive film. Such a transparent conductive film has the advantage of excellent flexibility. On the other hand, the conductive layer containing metal fibers has low contact resistance, and the conductive film having the conductive layer has a problem that it is prone to poor conductivity during transportation, storage, etc. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2009-505358 Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made to solve the above-mentioned problems, and its object is to provide a transparent conductive film that has a conductive layer containing metal fibers, yet is less likely to suffer from poor conductivity due to contact. [Means for solving the problem]

[0006] The transparent conductive film of the present invention comprises a substrate and a transparent conductive layer disposed on at least one side of the substrate, the transparent conductive layer comprising a polymer matrix and metal fibers present in the polymer matrix, and the transparent conductive layer has an arithmetic mean surface roughness Ra of 1.5 nm or more. In one embodiment, the metal fibers are metal nanowires. In one embodiment, the metal nanowires are silver nanowires. In one embodiment, the transparent conductive film further comprises a metal layer. In one embodiment, the metal layer is composed of copper. In one embodiment, the transparent conductive layer has a thickness of 50 nm to 300 nm. Effect of the Invention

[0007] According to the present invention, it is possible to provide a transparent conductive film which is unlikely to suffer from poor conductivity due to contact while having a conductive layer containing metal fibers. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a transparent conductive film according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] A. Overall structure of transparent conductive film 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. The transparent conductive film 100 includes a substrate 10 and a transparent conductive layer 20 disposed on at least one side (both sides in the illustrated example) of the substrate 10. The transparent conductive layer 20 includes a polymer matrix and metal fibers present in the polymer matrix. Although not illustrated, the transparent conductive film may further include any other appropriate layers. In one embodiment, at least one outermost layer of the transparent conductive film is a transparent conductive layer.

[0010] 2(a) and (b) are schematic cross-sectional views of a transparent conductive film according to another embodiment of the present invention. In the transparent conductive film 200, a transparent conductive layer 20 is disposed on only one side of a substrate 10. The transparent conductive film 300 further includes a metal layer 30. In the example of FIG. 2(b), the transparent conductive film 300 includes a metal layer 20, a substrate 10, and a metal layer 30 disposed in this order.

[0011] In the present invention, the arithmetic mean surface roughness Ra of the transparent conductive layer is 1.5 nm or more. By setting the arithmetic mean surface roughness Ra of the transparent conductive layer to the above range, a transparent conductive film that is unlikely to cause poor conductivity even when contact occurs with the transparent conductive layer can be obtained. When conventional transparent conductive films are provided in the form of a roll, frictional force is applied to the surface by contact with each other, and when a transparent conductive layer containing metal fibers is provided, the bonding between the metal fibers is easily released and poor conductivity occurs. On the other hand, even when the transparent conductive film of the present invention is provided in the form of a roll, the bonding between the metal fibers is maintained and the desired conductivity is maintained. In addition, even if the transparent conductive film is a sheet, the bonding between the metal fibers due to contact, friction, etc. when the transparent conductive film is laminated can be prevented. In addition, the transparent conductive film can exhibit excellent contact resistance not only to contact between transparent conductive films, but also to contact with other objects. The transparent conductive layer has an arithmetic mean surface roughness Ra of preferably 2.0 nm to 5.0 nm, more preferably 3.0 nm to 4.0 nm, and further preferably 3.0 nm to 3.5 nm. Within such a range, the above effects are significant. The arithmetic mean surface roughness Ra can be measured using an atomic force microscope.

[0012] The surface resistance value of the transparent conductive film of the present invention is preferably 0.01 Ω / □ to 1000 Ω / □, more preferably 0.1 Ω / □ to 500 Ω / □, particularly preferably 0.1 Ω / □ to 300 Ω / □, and most preferably 0.1 Ω / □ to 100 Ω / □. In one embodiment, the surface resistance value of the transparent conductive film is 100 Ω / □ or less.

[0013] The haze value of the transparent conductive film of the present invention is preferably 1% or less, more preferably 0.7% or less, and further preferably 0.5% or less. The smaller the haze value, the more preferable it is, and the lower limit thereof is, for example, 0.05%.

[0014] The total light transmittance of the transparent conductive film of the present invention is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more.

[0015] The thickness of the transparent conductive film of the present invention is preferably 10 μm to 500 μm, more preferably 15 μm to 300 μm, and further preferably 20 μm to 200 μm.

[0016] B.Transparent conductive layer As described above, the transparent conductive layer includes metal fibers and a polymer matrix.

[0017] The transparent conductive layer has a thickness of preferably 50 nm to 300 nm, and more preferably 80 nm to 200 nm. By making the thickness of the transparent conductive layer 50 nm or more, a transparent conductive layer having a small dynamic friction coefficient can be formed.

[0018] The total light transmittance of the transparent conductive layer is preferably 85% or more, more preferably 90% or more, and even more preferably 95% or more.

[0019] The dynamic friction coefficient of the transparent conductive layer against the transparent conductive layer is preferably 2.0 or less, more preferably 1.8 or less, even more preferably 1.5 or less, even more preferably 1.2 or less, particularly preferably 1.0 or less, and most preferably 0.8 or less. The dynamic friction coefficient of the transparent conductive layer against the transparent conductive layer is preferably as small as possible, and the lower limit is, for example, 0.05. Within this range, a transparent conductive film that is unlikely to cause poor conductivity even when contact with the transparent conductive layer occurs can be obtained. The "dynamic friction coefficient of the transparent conductive layer against the transparent conductive layer" refers to the dynamic friction coefficient between the transparent conductive layer of the transparent conductive film and a transparent conductive layer of the same composition as the transparent conductive layer of the transparent conductive film. In this specification, the dynamic friction coefficient is measured in accordance with JIS K7125:1999, with a measurement load of 100 g, a measurement speed of 1 mm / s, and a measurement distance of 30 mm.

[0020] In one embodiment, the dynamic friction coefficient when the transparent conductive layer and the surface opposite the transparent conductive layer are in contact with each other is preferably 2.0 or less, more preferably 1.8 or less, even more preferably 1.5 or less, even more preferably 1.2 or less, particularly preferably 1.0 or less, and most preferably 0.8 or less. The dynamic friction coefficient when the transparent conductive layer and the surface opposite the transparent conductive layer are in contact with each other is preferably smaller, and the lower limit is, for example, 0.05. The "surface opposite the transparent conductive layer" means the outermost surface opposite to the surface of the transparent conductive layer to be measured, based on the substrate. Therefore, when the transparent conductive film has a configuration of transparent conductive layer A / substrate / transparent conductive layer A, the "dynamic friction coefficient when the transparent conductive layer and the surface opposite the transparent conductive layer are in contact with each other" is the dynamic friction coefficient when transparent conductive layers (transparent conductive layer A and transparent conductive layer A) are in contact with each other, and is synonymous with the "dynamic friction coefficient of the transparent conductive layer against the transparent conductive layer". In addition, when the transparent conductive film has a transparent conductive layer / substrate structure, the "dynamic friction coefficient when the transparent conductive layer is brought into contact with the surface opposite to the transparent conductive layer" refers to the dynamic friction coefficient when the transparent conductive layer is brought into contact with the substrate. If the dynamic friction coefficient when the transparent conductive layer is brought into contact with the surface opposite to the transparent conductive layer is within the above range, the occurrence of poor electrical conductivity can be significantly prevented when the transparent conductive film is laminated or rolled.

[0021] In one embodiment, the transparent conductive layer is patterned. As a patterning method, any appropriate method can be adopted depending on the form of the transparent conductive layer. The shape of the pattern of the transparent conductive layer can be any appropriate shape depending on the application. For example, the patterns described in JP-T-2011-511357, JP-A-2010-164938, JP-A-2008-310550, JP-T-2003-511799, and JP-T-2010-541109 can be mentioned. After the transparent conductive layer is formed on the substrate, it can be patterned using any appropriate method depending on the form of the transparent conductive layer.

[0022] As the metal fiber, a metal nanowire can be preferably used. The metal nanowire is a conductive material made of metal, shaped like a needle or thread, and having a diameter of nanometer size. The metal nanowire may be straight or curved. If a transparent conductive layer made of metal nanowires is used, the metal nanowires become a mesh and are joined together to form a good electrical conduction path, so that a transparent conductive film with low electrical resistance can be obtained.

[0023] The ratio of the thickness d to the length L of the metal nanowire (aspect ratio: L / d) is preferably 10 to 100,000, more preferably 50 to 100,000, and particularly preferably 100 to 10,000. By using metal nanowires with such a large aspect ratio, the metal nanowires can be well crossed, and a small amount of metal nanowires can exhibit high conductivity. As a result, a transparent conductive film with high light transmittance can be obtained. In this specification, the "thickness of the metal nanowire" means the diameter when the cross section of the metal nanowire is circular, means the minor axis when the cross section is elliptical, and means the longest diagonal when the cross section is polygonal. The thickness and length of the metal nanowire can be confirmed by a scanning electron microscope or a transmission electron microscope.

[0024] The thickness of the metal nanowires is preferably less than 500 nm, more preferably less than 200 nm, particularly preferably 10 to 100 nm, and most preferably 10 to 60 nm. Within such a range, a transparent conductive layer with high light transmittance can be formed.

[0025] The length of the metal nanowires is preferably 1 μm to 1000 μm, more preferably 1 μm to 500 μm, and particularly preferably 1 μm to 100 μm. If the length is within this range, a transparent conductive film with high conductivity can be obtained.

[0026] Any suitable metal may be used as the metal constituting the metal nanowires, so long as it is a metal with high electrical conductivity. Examples of metals constituting the metal nanowires include silver, gold, copper, and nickel. Materials obtained by plating these metals (e.g., gold plating) may also be used. The metal nanowires are preferably made of one or more metals selected from the group consisting of gold, platinum, silver, and copper. In one embodiment, the metal nanowires are silver nanowires.

[0027] Any suitable method may be adopted as the method for producing the metal nanowires. For example, a method of reducing silver nitrate in a solution, a method of applying a voltage or current from the tip of a probe to the surface of a precursor, drawing out the metal nanowire at the tip of the probe, and continuously forming the metal nanowire may be mentioned. In the method of reducing silver nitrate in a solution, silver nanowires may be synthesized by liquid-phase reduction of silver salts such as silver nitrate in the presence of polyols such as ethylene glycol and polyvinylpyrrolidone. Silver nanowires of uniform size can be mass-produced according to the methods described in, for example, Xia, Y. et al., Chem. Mater. (2002), 14, 4736-4745 and Xia, Y. et al., Nano letters (2003) 3(7), 955-960.

[0028] The content of the metal nanowires in the transparent conductive layer is preferably 80% by weight or less, based on the total weight of the transparent conductive layer. Within this range, a transparent conductive layer having a small dynamic friction coefficient can be formed. The content of the metal nanowires in the transparent conductive layer is more preferably 30% by weight to 75% by weight, more preferably 30% by weight to 65% by weight, and even more preferably 45% by weight to 65% by weight, based on the total weight of the transparent conductive layer. Within this range, a transparent conductive film having excellent electrical conductivity and light transparency can be obtained.

[0029] Any suitable polymer may be used as the polymer constituting the polymer matrix. Examples of the polymer include acrylic polymers, polyester polymers such as polyethylene terephthalate, aromatic polymers such as polystyrene, polyvinyl toluene, polyvinyl xylene, polyimide, polyamide, and polyamideimide, polyurethane polymers, epoxy polymers, polyolefin polymers, acrylonitrile-butadiene-styrene copolymers (ABS), cellulose, silicon polymers, polyvinyl chloride, polyacetate, polynorbornene, synthetic rubber, and fluorine-based polymers. Preferably, a curable resin (preferably an ultraviolet-curable resin) composed of a polyfunctional acrylate such as pentaerythritol triacrylate (PETA), neopentyl glycol diacrylate (NPGDA), dipentaerythritol hexaacrylate (DPHA), dipentaerythritol pentaacrylate (DPPA), and trimethylolpropane triacrylate (TMPTA) is used.

[0030] The density of the transparent conductive layer is preferably 1.3 g / cm 3 ~10.5g / cm 3 and more preferably 1.5 g / cm 3 ~3.0g / cm 3 Within such a range, a transparent conductive film having excellent electrical conductivity and light transmittance can be obtained.

[0031] The transparent conductive layer can be formed by applying a conductive layer-forming composition containing metal fibers (e.g., metal nanowires) to a substrate (or a laminate of a substrate and another layer) and then drying the applied layer. The conductive layer-forming composition may contain a resin material that forms a polymer matrix. Alternatively, the resin material that forms the polymer matrix may be prepared separately from the conductive layer-forming composition, and after applying and drying the conductive layer-forming composition, a resin material (polymer composition, monomer composition) may be applied onto the layer composed of metal fibers, and then the applied layer of the resin material may be dried or cured to form a transparent conductive layer.

[0032] The conductive layer forming composition may contain any suitable solvent in addition to metal fibers (e.g., metal nanowires). The conductive layer forming composition may be prepared as a dispersion of metal fibers (e.g., metal nanowires). Examples of the solvent include water, alcohol-based solvents, ketone-based solvents, ether-based solvents, hydrocarbon-based solvents, aromatic solvents, and the like. From the viewpoint of reducing environmental load, it is preferable to use water. The conductive layer forming composition may further contain any suitable additive depending on the purpose. Examples of the additive include a corrosion inhibitor that prevents corrosion of metal fibers (e.g., metal nanowires), a surfactant that prevents aggregation of metal fibers (e.g., metal nanowires), and the like. The type, number, and amount of the additive used may be appropriately set depending on the purpose.

[0033] The dispersion concentration of the metal fibers (e.g., metal nanowires) in the conductive layer-forming composition is preferably 0.1% by weight to 1% by weight. Within this range, a transparent conductive layer having excellent conductivity and light transmittance can be formed.

[0034] Any appropriate method may be adopted as a method for applying the conductive layer-forming composition. Examples of the application method include spray coating, bar coating, roll coating, die coating, inkjet coating, screen coating, dip coating, letterpress printing, intaglio printing, and gravure printing. Any appropriate drying method (e.g., natural drying, air drying, heat drying) may be adopted as a method for drying the coating layer. For example, in the case of heat drying, the drying temperature is typically 50°C to 200°C, and preferably 80°C to 150°C. The drying time is typically 1 to 10 minutes.

[0035] The polymer solution contains a polymer that constitutes the polymer matrix, or a precursor of the polymer (a monomer that constitutes the polymer).

[0036] The polymer solution may contain a solvent. Examples of the solvent contained in the polymer solution include alcohol-based solvents, ketone-based solvents, tetrahydrofuran, hydrocarbon-based solvents, and aromatic solvents. The solvent is preferably volatile. The boiling point of the solvent is preferably 200°C or less, more preferably 150°C or less, and even more preferably 100°C or less.

[0037] C. Base material The substrate is typically made of any suitable resin. Examples of the resin constituting the substrate include cycloolefin resins, polyimide resins, polyvinylidene chloride resins, polyvinyl chloride resins, polyethylene terephthalate resins, and polyethylene naphthalate resins. Cycloolefin resins are preferably used. If a substrate made of a cycloolefin resin is used, a transparent conductive film having excellent flexibility can be obtained.

[0038] As the cycloolefin resin, for example, polynorbornene can be preferably used. Polynorbornene refers to a (co)polymer obtained by using a norbornene-based monomer having a norbornene ring as a part or all of the starting material (monomer). As the polynorbornene, various products are commercially available. Specific examples include "ZEONEX" and "ZEONOR" manufactured by Zeon Corporation, "Arton" manufactured by JSR Corporation, "TOPUS" manufactured by TICONA, and "APEL" manufactured by Mitsui Chemicals, Inc.

[0039] The glass transition temperature of the resin constituting the above-mentioned substrate is preferably 50° C. to 200° C., more preferably 60° C. to 180° C., and further preferably 70° C. to 160° C. If the substrate has a glass transition temperature in such a range, deterioration during formation of the transparent conductive laminate can be prevented.

[0040] The thickness of the substrate is preferably 8 μm to 500 μm, more preferably 10 μm to 250 μm, further preferably 10 μm to 150 μm, and particularly preferably 15 μm to 100 μm.

[0041] The total light transmittance of the substrate is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. Within such a range, a transparent conductive film suitable for use in a touch panel or the like can be obtained.

[0042] The substrate may further contain any suitable additive as necessary. Specific examples of additives include plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, UV absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, and thickeners. The type and amount of additives used may be appropriately set according to the purpose.

[0043] If necessary, various surface treatments may be performed on the substrate. Any suitable method may be adopted for the surface treatment depending on the purpose. For example, low pressure plasma treatment, ultraviolet irradiation treatment, corona treatment, flame treatment, acid or alkali treatment may be mentioned. In one embodiment, the transparent substrate is surface-treated to make the surface of the transparent substrate hydrophilic. By making the substrate hydrophilic, the processability when applying the transparent conductive layer forming composition prepared from an aqueous solvent is excellent. In addition, a transparent conductive film having excellent adhesion between the substrate and the transparent conductive layer can be obtained.

[0044] D. Metal layer The metal layer is comprised of any suitable metal, preferably a conductive metal such as silver, gold, copper, nickel, etc. In one embodiment, the metal layer is comprised of copper.

[0045] The metal layer can be formed by any appropriate method, such as a dry process (dry method) such as a vapor deposition method, a sputtering method, or CVD, or a wet process such as plating. EXAMPLES

[0046] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples in any way.

[0047] [Production Example 1] (Production of metal nanowires) In a reaction vessel equipped with a stirrer, 5 ml of anhydrous ethylene glycol and 0.5 ml of anhydrous ethylene glycol solution of PtCl2 (concentration: 1.5×10-4 mol / L) were added at 160°C. After 4 minutes, 2.5 ml of anhydrous ethylene glycol solution of AgNO3 (concentration: 0.12 mol / l) and 5 ml of anhydrous ethylene glycol solution of polyvinylpyrrolidone (MW: 55000) (concentration: 0.36 mol / l) were simultaneously added dropwise to the resulting solution over 6 minutes. After this addition, the solution was heated to 160°C for more than 1 hour to react until AgNO3 was completely reduced, producing silver nanowires. Next, acetone was added to the reaction mixture containing the silver nanowires obtained as described above until the volume of the reaction mixture was 5 times that of the reaction mixture, and the reaction mixture was centrifuged (2000 rpm, 20 minutes) to obtain silver nanowires. The silver nanowires (concentration: 0.2% by weight) and pentaethylene glycol dodecyl ether (concentration: 0.1% by weight) were dispersed in pure water to prepare a silver nanowire ink.

[0048] [Example 1] The silver nanowire ink obtained in Production Example 1 was applied onto a substrate (cycloolefin film) using a wire bar so that the resistivity after film formation would be 50 Ω / □, and the film was formed by heating at 120° C. for 2 minutes. Furthermore, a photocurable resin mainly composed of urethane acrylate was diluted to a solid concentration of 1.5% with a mixed solvent of isopropanol (IPA) and diacetone alcohol (DAA) (mixture ratio (by weight) IPA:DAA = 8:2) to prepare coating solution a. This was applied to the silver nanowire ink-coated surface using a spin coater so that the dry film thickness would be 70 nm, and after heating at 80 °C for 1 minute, it was exposed to an integrated exposure of 450 mJ / cm using a high-pressure mercury lamp. 2The resultant film was exposed to ultraviolet light of 1000 ohms to form a transparent conductive layer A, thereby obtaining a transparent conductive film A consisting of the substrate and the transparent conductive layer A. The transparent conductive film A was subjected to the following evaluations. (1) Dynamic friction coefficient against transparent conductive layer A Using a product named "TSf-503" manufactured by Kyowa Interface Science Co., Ltd., the dynamic friction coefficient was measured in accordance with JIS K7125:1999 by sliding transparent conductive layer A against transparent conductive layer A under the following conditions: sample (transparent conductive layer A) size on the contact side: 1 cm□, measurement load: 100 g, measurement speed: 1 mm / s, measurement distance: 30 mm, measurement temperature: 23°C. (2) Coefficient of static friction Using a product named "TSf-503" manufactured by Kyowa Interface Science Co., Ltd., transparent conductive layer A was slid against transparent conductive layer A in accordance with JIS K7125:1999 under the conditions of sample (transparent conductive layer A) size on the contact side: 1 cm□, measurement load: 100 g, measurement speed: 1 mm / s, measurement distance: 30 mm, and measurement temperature: 23°C, and the friction coefficient at the start of sliding (static friction coefficient) was measured. (3) Resistance increase rate The transparent conductive layers A were caused to slide against each other once over a distance of 3 cm under the same conditions as those used in measuring the dynamic friction coefficient, except that the load was 300 g. The surface resistance of the transparent conductive layer was measured for the above-mentioned rubbed area and other areas using a non-contact surface resistance measuring device (manufactured by NAPSON, product name "EC-80", sheet resistance measurement mode, room temperature: 26°C). The rate of increase in resistance due to sliding was calculated using the formula: (surface resistance of the sliding area / surface resistance of the area other than the sliding area). (4) Arithmetic mean roughness Ra of transparent conductive layer A The arithmetic mean roughness Ra of the surface of the transparent conductive layer A in an area of ​​5 μm×5 μm was measured using a scanning probe microscope “Nanoscope IV” AFM tapping mode manufactured by Veeco Instruments.

[0049] [Reference example 1-1] In the same manner as in Example 1, a transparent conductive film A was obtained. (1a) Dynamic friction coefficient against a copper film on a transparent conductive layer A Separately, a transparent conductive film A was obtained in the same manner as in Example 1. A copper film was formed by sputtering on the transparent conductive layer A of the obtained transparent conductive film A so as to have a thickness of 100 nm, thereby obtaining a copper film-attached transparent conductive film. Using this copper film-attached transparent conductive film as a sample on the contact side, the transparent conductive layer A and the copper film on the transparent conductive layer A were slid against each other in the same manner as in (1) above, and the dynamic friction coefficient was measured. (2a) Coefficient of static friction Separately, a transparent conductive film A was obtained in the same manner as in Example 1. A copper film was formed by sputtering on the transparent conductive layer A of the obtained transparent conductive film A so as to have a thickness of 100 nm, thereby obtaining a copper film-attached transparent conductive film. Using this copper film-attached transparent conductive film as a sample on the contact side, the transparent conductive layer A and the copper film on the transparent conductive layer A were slid against each other in the same manner as in (2) above, and the coefficient of friction (static coefficient of friction) at the start of sliding was measured. (3a) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer A and the copper film on the transparent conductive layer A were caused to slide against each other, and the rate of increase in resistance value due to the sliding was measured. (4a) Arithmetic mean roughness Ra of the copper film on the transparent conductive layer A The arithmetic mean roughness Ra of the copper film on the transparent conductive layer A was measured by the same method as in (4) above.

[0050] [Reference example 1-2] In the same manner as in Example 1, a transparent conductive film A was obtained. (1b) Dynamic friction coefficient against transparent conductive layer d The silver nanowire ink obtained in Production Example 1 was applied onto a substrate (cycloolefin film) using a wire bar so that the resistivity after film formation would be 50 Ω / □, and the film was formed by heating at 120° C. for 2 minutes. Furthermore, a photocurable resin mainly composed of urethane acrylate was diluted with methyl isobutyl ketone to a solid content concentration of 1.5% to prepare coating solution a. This was applied to the silver nanowire ink-coated surface using a spin coater so that the dry film thickness would be 70 nm, and after heating at 80°C for 1 minute, it was exposed to a high-pressure mercury lamp with an integrated exposure dose of 450 mJ / cm. 2The resultant was exposed to ultraviolet light of 1000 nm to form a transparent conductive layer d, thereby obtaining a transparent conductive film d consisting of the substrate / transparent conductive layer d. Using the transparent conductive film d as the sample on the contact side, the transparent conductive layer A and the transparent conductive layer d were slid against each other in the same manner as in (1) above to measure the dynamic friction coefficient. (2b) Coefficient of static friction Using transparent conductive film d as the sample on the contact side, transparent conductive layer A and transparent conductive layer d were slid against each other in the same manner as in (2) above, and the initial friction coefficient (static friction coefficient) was measured. (3b) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer A and the transparent conductive layer d were caused to slide against each other, and the rate of increase in resistance value due to the sliding was measured. (4b) Arithmetic mean roughness Ra of transparent conductive layer d The arithmetic mean roughness Ra of the transparent conductive layer d was measured by the same method as in (4) above.

[0051] [Reference example 1-3] In the same manner as in Example 1, a transparent conductive film A was obtained. (1c) Dynamic friction coefficient against cycloolefin film The contact side sample was a cycloolefin film (manufactured by Zeon Corporation, product name "ZF16"), and the transparent conductive layer A and the cycloolefin film were slid against each other in the same manner as in (1) above to measure the dynamic friction coefficient. (2c) Coefficient of static friction The sample on the contact side was a cycloolefin film (manufactured by Zeon Corporation, product name "ZF16"), and the transparent conductive layer A and the cycloolefin film were slid against each other in the same manner as in (2) above, to measure the initial friction coefficient (static friction coefficient). (3c) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer A and the cycloolefin film were caused to slide against each other, and the rate of increase in resistance due to the sliding was measured. (4c) Arithmetic mean roughness Ra of cycloolefin film The arithmetic mean roughness Ra of the cycloolefin film was measured by the same method as in (4) above.

[0052] [Reference example 1-4] In the same manner as in Example 1, a transparent conductive film A was obtained. (1d) Dynamic friction coefficient against PET film The contact side sample was a PET film (manufactured by KOLON industry, product name "CE900"), and the transparent conductive layer A and the PET film were slid against each other in the same manner as in (1) above to measure the dynamic friction coefficient. (2d) Coefficient of static friction The sample on the contact side was a PET film (manufactured by KOLON industry, product name "CE900"), and the transparent conductive layer A and the PET film were slid against each other in the same manner as in (2) above, to measure the initial friction coefficient (static friction coefficient). (3d) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer A and the PET film were caused to slide against each other, and the rate of increase in resistance value due to the sliding was measured. (4d) Arithmetic mean roughness Ra of PET film The arithmetic mean roughness Ra of the PET film was measured by the same method as in (4) above.

[0053] [Reference example 1-5] In the same manner as in Example 1, a transparent conductive film A was obtained. (1e) Coefficient of kinetic friction against acrylic film The contact side sample was an acrylic film (manufactured by Toyo Kohan Co., Ltd., product name "HX-40-UF"), and the transparent conductive layer A and the acrylic film were slid against each other in the same manner as in (1) above to measure the dynamic friction coefficient. (2e) Coefficient of static friction The sample on the contact side was an acrylic film (manufactured by Toyo Kohan Co., Ltd., product name "HX-40-UF"), and the transparent conductive layer A and the acrylic film were slid against each other in the same manner as in (2) above, to measure the initial friction coefficient (static friction coefficient). (3e) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer A and the acrylic film were caused to slide against each other, and the rate of increase in resistance value due to the sliding was measured. (4e) Arithmetic mean roughness Ra of acrylic film The arithmetic mean roughness Ra of the acrylic film was measured by the same method as in (4) above.

[0054] [Example 2] A transparent conductive film B composed of a substrate and a transparent conductive layer B was obtained in the same manner as in Example 1, except that the dry film thickness of the coating solution a was set to 100 nm. Transparent conductive film B was subjected to the following evaluations. (1B) Dynamic friction coefficient against transparent conductive layer B Using a product named "TSf-503" manufactured by Kyowa Interface Science Co., Ltd., the dynamic friction coefficient was measured in accordance with JIS K7125:1999 by sliding transparent conductive layer B against transparent conductive layer B under the following conditions: sample size (transparent conductive layer B) on the contact side: 1 cm□, measurement load: 100 g, measurement speed: 1 mm / s, measurement distance: 30 mm, measurement temperature: 23°C. (2B) Coefficient of static friction Using a product named "TSf-503" manufactured by Kyowa Interface Science Co., Ltd., transparent conductive layer B was slid against transparent conductive layer B in accordance with JIS K7125:1999 under the following conditions: sample size (transparent conductive layer B) on the contact side: 1 cm□, measurement load: 100 g, measurement speed: 1 mm / s, measurement distance: 30 mm, measurement temperature: 23°C, and the friction coefficient at the start of sliding (static friction coefficient) was measured. (3B) Resistance increase rate The transparent conductive layers B were caused to slide against each other once over a distance of 3 cm under the same conditions as those used in measuring the dynamic friction coefficient, except that the load was 300 g. The surface resistance of the transparent conductive layer was measured for the above-mentioned rubbed area and other areas using a non-contact surface resistance measuring device (manufactured by NAPSON, product name "EC-80", sheet resistance measurement mode, room temperature: 26°C). The rate of increase in resistance due to sliding was calculated using the formula: (surface resistance of the sliding area / surface resistance of the area other than the sliding area). (4B) Arithmetic mean roughness Ra of transparent conductive layer B The arithmetic mean roughness Ra of the surface of the transparent conductive layer B was measured in an area of ​​5 μm×5 μm using a scanning probe microscope “Nanoscope IV” AFM tapping mode manufactured by Veeco Instruments.

[0055] [Comparative Example 1] A silver nanowire layer was formed in the same manner as in Example 1. Furthermore, a silane coupling agent was added to a photocurable resin mainly composed of urethane acrylate, and the coating solution c was prepared by diluting the resin with methyl isobutyl ketone to a solid content concentration of 1.5%, and the coating solution c was applied to the silver nanowire ink-coated surface using a spin coater so that the dry film thickness would be 70 nm, and the coating was heated at 80° C. for 1 minute, and then exposed to a high-pressure mercury lamp with an integrated exposure dose of 450 mJ / cm 2 . 2 The substrate was irradiated with ultraviolet light of 1000 nm to form a transparent conductive layer C, thereby obtaining a transparent conductive film C consisting of the substrate / transparent conductive layer C. (1f) Dynamic friction coefficient against transparent conductive layer d The contact side sample was made of transparent conductive layer C, and the transparent conductive layer C was slid against another transparent conductive layer C in the same manner as in (1) above to measure the dynamic friction coefficient. (2g) Coefficient of static friction The contact side sample was made of transparent conductive layer C, and the transparent conductive layer c and the transparent conductive layer C were slid against each other in the same manner as in (2) above, to measure the initial friction coefficient (static friction coefficient). (3g) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer C and the cycloolefin film were caused to slide against each other, and the rate of increase in resistance due to the sliding was measured. (4g) Arithmetic mean roughness Ra of transparent conductive layer d The arithmetic mean roughness Ra of the transparent conductive layer C was measured by the same method as in (4) above.

[0056] [Comparative Example 2] A transparent conductive film d consisting of a substrate / transparent conductive layer d was obtained in the same manner as in Reference Example 1-2. (1g) Dynamic friction coefficient against transparent conductive layer d The contact side sample was treated as a transparent conductive layer d, and the dynamic friction coefficient was measured by sliding the transparent conductive layer d against another transparent conductive layer d in the same manner as in (1) above. (2g) Coefficient of static friction The contact side sample was treated as transparent conductive layer d, and transparent conductive layer d was slid against transparent conductive layer d in the same manner as in (2) above, to measure the initial friction coefficient (static friction coefficient). (3g) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer d and the cycloolefin film were caused to slide against each other, and the rate of increase in resistance due to the sliding was measured. (4g) Arithmetic mean roughness Ra of transparent conductive layer d The arithmetic mean roughness Ra of the transparent conductive layer d was measured by the same method as in (4) above.

[0057] [Comparative Reference Example 2-1] In the same manner as in Comparative Example 2, a transparent conductive film d was obtained. (1h) Dynamic friction coefficient against a copper film on a transparent conductive layer d Separately, a transparent conductive film d was obtained in the same manner as in Comparative Example 2. A copper film was formed by sputtering on the transparent conductive layer d of the obtained transparent conductive film d so as to have a thickness of 100 nm, to obtain a copper-film-attached transparent conductive film. Using this copper-film-attached transparent conductive film as a sample on the contact side, the transparent conductive layer d and the copper film on the transparent conductive layer d were slid against each other in the same manner as in (1) above, and the dynamic friction coefficient was measured. (2h) Coefficient of static friction The contact side sample was the above-mentioned transparent conductive film with copper film, and the transparent conductive layer d was slid against the copper film on the transparent conductive layer d in the same manner as in (2) above, and the initial friction coefficient (static friction coefficient) was measured. (3h) Resistance increase rate In the same manner as in (3) above, the transparent conductive layer d and the copper film on the transparent conductive layer d were caused to slide against each other, and the rate of increase in resistance value due to the sliding was measured. (4h) Arithmetic mean roughness Ra of the copper film on the transparent conductive layer d The arithmetic mean roughness Ra of the copper film on the transparent conductive layer d was measured by the same method as in (4) above.

[0058] The evaluation results of the above-mentioned Examples, Reference Examples, Comparative Examples, and Comparative Reference Examples are shown in Table 1. In addition, the sample on the contact side for the dynamic friction coefficient and resistance increase rate is indicated in the table as "layer in contact with transparent conductive layer." [Table 1]

[0059] As is clear from Table 1, according to the present invention, by specifying the arithmetic mean surface roughness Ra of the transparent conductive layer, it is possible to provide a transparent conductive film that is unlikely to cause poor conductivity due to contact, even though it has a conductive layer containing metal fibers. As shown in the reference examples, such a transparent conductive film is able to suppress an increase in resistance value even when it comes into contact with and slides against various films, etc. [Explanation of symbols]

[0060] 10 Base material 20 Transparent conductive layer 30 metal layer 100, 200, 300 Transparent conductive film

Claims

1. A substrate and a transparent conductive layer disposed on at least one side of the substrate, the transparent conductive layer comprises a polymer matrix and metal fibers present in the polymer matrix; The transparent conductive layer has an arithmetic average surface roughness Ra of 1.5 nm or more. Transparent conductive film.

2. The transparent conductive film according to claim 1 , wherein the metal fibers are metal nanowires.

3. The transparent conductive film according to claim 2 , wherein the metal nanowires are silver nanowires.

4. The transparent conductive film according to claim 1 , further comprising a metal layer.

5. The transparent conductive film of claim 4 , wherein the metal layer is made of copper.

6. 6. The transparent conductive film according to claim 1, wherein the transparent conductive layer has a thickness of 50 nm to 300 nm.

Citation Information

Patent Citations

  • Transparent conductive film, method for manufacturing transparent conductive film, and intermediate

    JP2021037668A

  • Transparent electrode and method for producing same

    WO2015025792A1

  • Transparent conductors based on nanowires

    JP2009505358A